Estimation of carbon dioxide emissions from the megafires of Australia in 2019–2020 - Tomohiro Shiraishi; Ryuichi Hirata (Scientific Reports, 2021)
Abstract Catastrophic fires occurred in Australia between 2019 and 2020. These fires burned vast areas and caused extensive damage to the environment and wildlife. In this study, we estimated the carbon dioxide (CO2) emissions from these fires using a bottom-up method involving the improved burnt area approach and up-to-date remote sensing datasets to create monthly time series distribution maps for Australia from January 2019 to February 2020. The highest monthly CO2 emissions in Australia since 2001 were recorded in December 2019. The estimated annual CO2 emissions from March 2019 to February 2020 in Australia were 806 ± 69.7 Tg CO2 year−1, equivalent to 1.5 times its total greenhouse gas emissions (CO2 equivalent) in 2017. New South Wales (NSW) emitted 181 ± 10.2 Tg CO2 month−1 in December 2019 alone, representing 64% of the average annual emissions of Australia from 2001–2018. The negative correlation observed between CO2 emissions and precipitation for 2001–2020 was 0.51 for Australia. Lower than average precipitation and fires in high biomass density areas caused significant CO2 emissions. This study helps to better assess the performance of climate models as a case study of one of the major events caused by climate.